Study of the effect of bulb seal on the slat noise using numerical simulation - Himeno, Fernando Henrique Tadashi (2018)
The development on Environmental Regulations related to aircraft noise propagated to the vicinity of airports forced the industry to investigate the noise sources and look for alternatives of noise reduction. The current aircraft noise has a large contribution provenient from the airframe, due to the turbofan engine development. One can identify the most relevant sources as the landing gear, flap and slat. Since slat is distributed in almost whole extension it becomes a distributed noise source. The presence of excrescences inside slat cove can changes significantly the recirculating flow and the characteristics of noise generated. We present simulations with PowerFLOW code for MD30P30N high-lift airfoil, with a square section seal attached on slat cove. Results of propagated noise are presented showing the presence of broadband peaks and the differences caused by the seal inclusion. Mean flow shows the presence of an additional recirculation bubble for some positions of the seal. Propor Orthogonal Decomposition was used to identify the coherent structures that could be related to the slat cavity modes and emerges at earlier stages of mixing layer for cases where the seal presence creates a secondary counter-rotating bubble